Study of Ozone Synthesis With Methods of Plasma Discharge - Rachmat Triandi Tjahjanto; Sri Wardhani; Ulfa Anggraini (Natural B, Journal of Health and Environmental Sciences, 2012)
In this research an ozonator prototype has been built to produce ozone, consists of air pump, gas flowmeter, an ozone reactor, and a glass pipe of nozzle. The most important part of the device is the reactor which consisting three main parts; 5 mm alloy electrode connected to a high voltage generator in the form of electrical gas stove lighter, 1 mm copper negative electrodes connected to the ground and a glass plasma discarge. The ozone gas formed is flowed to a container consisting of methyl orange solution 20 ppm at wave lenght of 470 nm. The concentration of ozone is determined by spectrophotometry method. The ozonator is characterized by ozonation periode variation of 5, 10, 15, 20, 25, and 30 minutes with the voltage used 3,5 volt, voltage variation of 3, 4, and 5 volts and flow rate variation of 227, 363, 464, 662, 864, and 1060 mL/min at the voltage used 3.5 volt. The result showed that the longer period and the higher voltage used for ozonation, the higher the ozone gas produced. The concentration of ozone obtained in this research is 0.76 ppm reached at 363 mL/min with 20 minutes ozonation duration.